TOURISM AND TECHNOLOGY: THE FUTURE - Nanda, Bhanu (2010)
Technology has a crucial impact on Tourism today. Tourism in itself is being shifted from visiting to experience based visiting and travelling. As per the existing literature, tourist’s inclination towards experience based touring has taken a rise and this might change the authentic behaviour of a tourist. However, mobile technology is gaining momentum and tourism sector is not left much behind in order to provide new technology for tourists through mobile phones. Thus the debate continues on the tourist use of digital media which leads to shift in authentic behaviour of the visitor.#